2015
DOI: 10.1051/fruits/2015030
|View full text |Cite
|
Sign up to set email alerts
|

Limiting brown rot incidence in peach with tree training and pruning

Abstract: -Introduction. To limit peach brown rot incidence in a mid-season peach orchard cv. 'Conquise', three combinations of tree training and pruning treatments were assessed: open vase training with conventional pruning (Control); open vase with centrifugal pruning (CentP); vertical axis training with centrifugal pruning (Axis). Materials and methods. The test orchard was divided into four blocks, each with the three tree management treatments in a randomized complete block design. Brown rot incidence as well as fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Our results indicate that agronomic practices based on regulated deficit irrigation and fruit thinning can provide effective control on the brown rot spreading, and eventually guarantee monetary returns similar to those that would be obtained in the absence of the disease, a situation that is actually achieved through the use of fungicides. Previous field observations indicated that agronomic practices play a role in the diffusion of brown rot: water deprivation and open vase training with centrifugal pruning were associated to lower brown rot incidence 25,3638 . Our modelling approach can help to identify which epidemiological processes are responsible for the observed patterns, and optimize the deployment of control strategies.…”
Section: Discussionmentioning
confidence: 96%
“…Our results indicate that agronomic practices based on regulated deficit irrigation and fruit thinning can provide effective control on the brown rot spreading, and eventually guarantee monetary returns similar to those that would be obtained in the absence of the disease, a situation that is actually achieved through the use of fungicides. Previous field observations indicated that agronomic practices play a role in the diffusion of brown rot: water deprivation and open vase training with centrifugal pruning were associated to lower brown rot incidence 25,3638 . Our modelling approach can help to identify which epidemiological processes are responsible for the observed patterns, and optimize the deployment of control strategies.…”
Section: Discussionmentioning
confidence: 96%
“…The worldwide agriculture has changed its cultivation systems to increase yield and quality (Lauri & Corelli-Grappadelli, 2014) of the crops. Such increasement is expected to be achieved with reduced inputs (Bussi et al, 2015) and labor requirements (Caracciolo et al, 2021;Loreti & Massai, 2002). The use of high-density orchards is adopted as an option to reach these goals and induce the plants to early production (Loreti & Massai, 2002;Pasa et al, 2017;Souza et al, 2019;Uberti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fungicide applications are necessary to diminish BR damage in humid seasons, but lead to sustainability challenges in pome and stone fruit cropping, as there are many fungicide-resistant strains (Monilinia fructicola, see below). An important research field has been dedicated to the epidemiology of BR, as well as aspects related to traditional chemical control and emerging alternative control strategies (e.g., tree management), , compatible with IPM and organic agriculture (biologic agents, postharvest biochemical–physical agents). These topics are thoroughly reviewed and discussed in recent publications. , Significant efforts are being invested to characterize and enhance fruit resistance to BR for the generation of new varieties with reduced requirements of application of exogenous methods for BR control.…”
Section: Introductionmentioning
confidence: 99%